Universities as Potential Social Agents in the Urban Regeneration of Fragile Local Communities: A Mutual Learning Process - Proença, Mariana Auad (2023)
Currently, the world is facing economic, social, and environmental issues in a more revolutionary and connected way than in previous years. One of the main challenges is identifying which, among possible actors considering their role in society, could be the leaders of future changes. Therefore, over the years, universities were progressively building and playing an essential role through new research strategies linked to social responsibility within communities by expanding research and teaching beyond the boundaries of the university campus. This work aims to provide concepts and ideas to induce a discussion and build critical thinking on how important it is to connect the work of universities with fragile local communities, in other words, to understand the social role of universities better. First, a general overview of social responsibility and territorial fragility concepts is presented. Then, university social networks and organizations and case analyses illustrate the importance of projects developed within communities, particularly with innovative educational practices, to search for urban regeneration and mutual learning between universities and society.